234 THE IMPACT OF OLDER AGE ON CLINICAL OUTCOMES DURING THE FIRST WAVE OF THE COVID-19 PANDEMIC. (18th November 2021) - Okpaje, B; Gabr, A; Mohamed, A; Teoh, T K; Mustafa, W; Saleh, A; Ali, B; Leahy, A; Stapelton, P; O'Connell, N; Power, L; O'Connell, S; et al.
Abstract: Background: Severe acute respiratory coronavirus 2 (SARS-CoV-2) was first recorded in Ireland in February 2020. Several studies have explored the association between age and SARS-CoV-2, showing that there were poorer outcomes in older people. Our objective was to evaluate the impact of age on outcomes such as hospital length of stay, mortality, and re-hospitalisation. Methods: We performed a single-centre, retrospective observational cohort study, using an electronic microbiology database of recorded index admissions of SARS-CoV-2 positive patients aged 65 years and older during SARS-CoV-2 wave one (March 1 st to May 31 st 2020). PCR testing of nasopharyngeal and/or sputum samples was used to confirm positivity. Our clinical outcomes measured included hospital length of stay, mortality and re-admission rate within 6 months. Results: 153 patients 65 years and above were admitted. The male to female ratio was 1.3 with 90% admitted medically. 79 patients were aged between 65–79 years; 84 patients ≥80 years; and 12 patients ≥90 years. Mortality was 25%, 31% and 42%, respectively. Median length of stay remained 14 days for ages 65–89 rising to 17.5 days for those ≥90 years. Re-hospitalisation rates at 6 months were similar for ages 65–79 and 89–89 years at 42% and 40%, respectively. One patient (14%) over 90 years was re-hospitalised. Conclusion: SARS-CoV-2 has disproportionately impacted on general medical services treating older hospitalised people. In our centre, mortality for patients ≥65 years was 28.1% which compared favourably with 35.6% internationally as outlined by Victor et al. (2020) based on Spanish data. Treatment of SARS-CoV-2 is not futile in older patients with 58% of nonagenarians and 69% of octogenarians surviving, however re-hospitalisation rates are high at 40%. A targeted approach to discharge support via integrated care may ameliorate this.